2016
DOI: 10.2139/ssrn.2836019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emissions-Based Taxes on the Retirement of Used and Inefficient Vehicles: The Case of Switzerland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Relevant information about this dataset can be found, together with further information, inAlberini et al (2015) andAlberini et al (2018).8 Between Jan 1. 2000 and Jan 1.…”
mentioning
confidence: 95%
“…Relevant information about this dataset can be found, together with further information, inAlberini et al (2015) andAlberini et al (2018).8 Between Jan 1. 2000 and Jan 1.…”
mentioning
confidence: 95%
“…They found that CO 2 differentiated registration tax contributes significantly to shifting purchase towards low -emitting cars. The authors [14] analysed the impact of different bonus/malus annual registration fee in Switzerland. The authors suggest that retirement of old cars can be reached through a bonus/malus scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Excise duty is considered to be the best available tool for reducing CO 2 emissions, as there is a direct correlation between the fuel consumption and emissions and it is also easily implemented in the tax system [1]. This tax induces a change in the behavior of both the motor vehicle manufacturers and the users and underestimates consumers in buying more fuel-efficient vehicles [2]. Other benefits of this tax can be seen in indirect distance travel taxation, and consumers have more opportunities to minimize this tax, for example by switching to a different mode of transport, a more economical driving style, or reduced mileage [3].…”
Section: Introductionmentioning
confidence: 99%
“…In our context, the concept of salience would apply only to the fraction of aware individuals that acknowledges the presence of the policy measure. and information on vehicle choices (D'Haultfoeuille et al, 2014, Klier and Linn, 2015, Alberini and Bareit, 2017, Alberini et al, 2018, Grigolon et al, 2018, Allcott and Knittel, 2019, Cerruti et al, 2019. We show a large lack of awareness by consumers about the presence of tax incentives for the purchase of an energy efficient vehicle.…”
Section: Introductionmentioning
confidence: 89%